The Effect of Robotic Programming Education on Learner’s Critical Thinking Skills at The Secondary School Level - Şeyma Betül Çelik; Muhammet Demirbilek (Interaction Design and Architecture(s))
This study aimed to determine the effectiveness of robotic programming education on learner’s thinking and critical thinking skills at the 6th-grade elementary school level. Student experiences were determined after each week. For this purpose, in the 2017-2018 academic year, four weeks of robotic programming training was applied to 20 students in the 6th grade of a public school in Uşak. The research was conducted by using video recording, critical thinking skill scales, and activity perception scales. At the end of the research, the findings obtained were included and suggestions were made for the inclusion of robotic programming in the education curriculum and the researchers and the application. In this study, one group pretest-posttest experimental model was used. In the analysis of quantitative data, a dependent samples t-test was used. As the process of adapting the perception of efficacy scale into Turkish was not fully concluded, the data obtained were interpreted on a substance-by-item basis. At the end of the study, a significant difference was found between the pre-test and post-test perception scores of the students in the experimental group. At the end of the activity perception scale, it was observed that students had positive experiences with robotic coding.